Selection and induction of rat skeletal muscle-derived cells to the chondro-osteogenic lineage. - Claros-Gil, Silvia; Alonso, Mónica; Becerra-Ratia, José; Andrades-Gómez, José Antonio (CMB Association, 2008)
Bone marrow (BM) has been long established as the main source of pluripotential mesenchymal stem cells (MSCs), and has been so far the main recognized source of osteoprogenitor cells that contribute to the turnover of the skeletal scaffold. The existence of an osteoprogenitor cell in other connective tissues such as skeletal muscle has been reported. In light of its availability and because of the relative ease of muscle cell isolation, skeletal muscle is an attractive source of cells for use in tissue engineering applications. The aim of this study was to explore the potential to differentiate into the chondro-osteoblastic lineage of a plastic adhering cell population, referred t as skeletal muscle-derived cells (SMDCs), obtained from biopsies of rat skeletal muscle. SMDCs displayed a fibroblast-like morphology. Our study revealed that the isolated cell population had a mesenchymal origin as indicated by abundant expression of STRO-1 and CD166. Osteogenic markers like osteocalcin (OC), bone sialoprotein (BSP)and osteopontin (OP) gene expressions were detected by RT-PCR. When these cells were cultured in the presence of an osteo-inductive culture medium, positive staining for alkaline phosphatase (ALP) and formation of mineralized matrix were increased. Furthermore SMDCs formed bone and cartilage tissues in vivo when placed inside of diffusion chambers and in demineralized bone matrix (DBM) cylinders, implanted subdermically into the backs of rat for 28 days. In conclusion, this experimental procedure is capable of selecting a cell population obtained from the skeletal muscle that is able to complete the differentiation pathway leading to the formation of cartilage and bone. In this respect SMDCs resemble BM stromal cells (BMSCs) and have demonstrated a potential application for cartilage and bone tissue engineering.
Política de acceso abierto tomada de: https://www.cellmolbiol.org/index.php/CMB/EditorialPolicies
Keywords: Células madre; Huesos - Crecimiento - Modelos animales; Skeletal muscle cells; Mesenchymal stem cells; Chondrogenesis; Osteogenesis; rhBMP-2; Demineralized bone matrix; Diffusion chamber; Rat